Text Treasures: The Pilgrimage of Egeria (The Biblical archaeology review, 2024)
Egeria’s Travels is an early Christian pilgrimage account by an educated and well-traveled woman from the Roman province of Galicia (in modern Spain) that tells of her journey to and around the Holy Land. Dating to the late fourth century, this work is a rich source of geographical and historical information. The account is unfortunately […]